2021
DOI: 10.3390/app11115068
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Irradiation-Induced Abnormal Development and DNA Damage in Phthorimaea operculella (Lepidoptera: Gelechiidae)

Abstract: The potato tuber moth, Phthorimaea operculella (Zeller), is a destructive pest of Solanaceous crops. This study investigated the effects of X-ray irradiation on development, DNA damage and recovery in P. operculella. Eggs, larvae (*3rd and 5th), pupae, and adults were irradiated with various doses of X-ray irradiation. Egg hatching was inhibited at 70 Gy, and the pupation and adult emergence of 3rd-instar larvae were inhibited at 150 Gy and 70 Gy, respectively. Some 5th-instar larvae pupated at 150 Gy but fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Since electron beam irradiation induces abnormal reproduction and development in insect pests depending on the insect species and stage of development, a large amount of basic data is required for ionizing radiation to be utilized for quarantine disinfection. In a previous study, many researchers reported the effects of gamma-ray, X-ray, and electron beam irradiation on Plutella xylostella (Linnaeus) (Lepidoptera: Plutellidae), Myzus persicae (Sulzer) (Hemiptera: Aphididae), Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae), Liriomyza trifolii (Burgess) (Diptera: Agromyzidae), Spodoptera litura (F.) (Lepidoptera: Noctuidae), Frankliniella intonsa (Trybom) (Thysanoptera: Thripidae), Drosophila suzukii (Matsumura) (Diptera: Drosophilidae), and Helicoverpa armigera Hübner (Lepidoptera: Noctuidae) [12][13][14][21][22][23][24][25][26][27][28]. In addition, intracellular DNA was also damaged by ionizing irradiation [19,20,28].…”
Section: Discussionmentioning
confidence: 99%
“…Since electron beam irradiation induces abnormal reproduction and development in insect pests depending on the insect species and stage of development, a large amount of basic data is required for ionizing radiation to be utilized for quarantine disinfection. In a previous study, many researchers reported the effects of gamma-ray, X-ray, and electron beam irradiation on Plutella xylostella (Linnaeus) (Lepidoptera: Plutellidae), Myzus persicae (Sulzer) (Hemiptera: Aphididae), Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae), Liriomyza trifolii (Burgess) (Diptera: Agromyzidae), Spodoptera litura (F.) (Lepidoptera: Noctuidae), Frankliniella intonsa (Trybom) (Thysanoptera: Thripidae), Drosophila suzukii (Matsumura) (Diptera: Drosophilidae), and Helicoverpa armigera Hübner (Lepidoptera: Noctuidae) [12][13][14][21][22][23][24][25][26][27][28]. In addition, intracellular DNA was also damaged by ionizing irradiation [19,20,28].…”
Section: Discussionmentioning
confidence: 99%